Characteristics of the archival fond of „Konvento Polonia aktai” from the Wróblewski Library of the Lithuanian Academy of Sciences - Dowgiało, Karol (Saeculum Christianum. Pismo Historyczne, 2021)
After World War II documentation of archive of the Konwent Polonia was dispersed. Currently, it is gathered in three institutions: The Archdiocesan Archive of Warsaw, The Wro-blewski Library of the Lithuanian Academy of Sciences in Vilnius and The Polish Institute and Sikorski Museum in London. This study presents a Vilnius collection – both structure of the archival fond and the information value of gathered archival units. It is extremely useful for researchers – particularly in the context of the lack of online inventories, as well as factual mistakes committed during the archival description of the records gathered there. This archival fond consists of 404 units and it is one of the most important sources for the history of both the Konwent Polonia and polish fraternities. Especially that most of fraternities archives were destroyed, and the total number of members of all academic fraternities until the outbreak of World War II was at least over a twelve thousand